Intraoperative bone marrow puncture in breast cancer patients: prospective assessment of adverse side-effects - Domschke, Christoph; Neubrech, Florian G.; Dick, Michelle; Rom, Joachim; Beckhove, Philipp; Sohn, Christof; Schütz, Florian; Scharf, Alexander (The breast, 2011)
Background and aim - In breast cancer patients, intraoperative bone marrow puncture (BMP) with positive detection of disseminated tumor cells has been reported to predict unfavorable clinical outcome due to increased risk of recurrence. In this study, we prospectively assessed BMP-associated untoward side-effects. - Methods - Fifty-eight consecutive breast cancer patients were prospectively explored after intraoperative BMP for postoperative pain (visual analogue scale, VAS) and complications in terms of infection, hematoma, and sensibility disorder. Furthermore, the impact of BMP on hospital stay duration was analyzed in 254 patients. - Results - In all subgroups analyzed, during five postoperative days patients complained about minor pain only at the site of BMP (VAS < 1) while the corresponding pain scores were significantly higher for the area of the operated breast. Post-BMP iliac crest hematomas were encountered in 13 out of 58 patients (22.4%) who were significantly older (p = 0.04), less frequently smokers (p = 0.02), and presented with higher body mass index (p = 0.01) than controls. Within the area of BMP no signs of infection or sensibility disorders were observed. Comparison of patients with and without BMP did not show any significant difference in postoperative hospital stay duration. - Conclusion - Referring to the potential clinical benefit of intraoperative BMP its prospectively assessed adverse side-effects appear relatively mild and thus acceptable.
Available online 10 July 2010
Gesehen am 20.06.2022